Recent research progress on imbibition system of nanoparticle-surfactant dispersions - Wenhao Shao; Jinzhou Yang; Haoyi Wang; Jiawei Chang; Hairong Wu; Jirui Hou (Capillarity, 2023)
Nanotechnology has been increasingly applied in the petroleum industry in recent years. In particular, dispersions consisting of nanoparticles and surfactants have been widely investigated. The imbibition system compounded by nanoparticle and surfactant was found to display a high efficiency in enhancing oil recovery. This paper briefly reviews the factors influencing imbibition efficiency. At the same time, the application and mechanism of the imbibition system of nanoparticle-surfactant dispersion in the field of enhanced oil recovery are introduced. Additionally, the limitations and challenges that the imbibition system of nanoparticle-surfactant dispersions may face in enhanced oil recovery applications are put forward. The current work reveals that the imbibition system with nanoparticle-surfactant dispersion is an ideal candidate for enhanced oil recovery in tight and low-permeability reservoirs. Document Type: Invited review Cited as: Shao, W., Yang, J., Wang, H., Chang, J., Wu, H., Hou, J. Recent research progress on imbibition system of nanoparticle-surfactant dispersions. Capillarity, 2023, 8(2): 34-44. https://doi.org/10.46690/capi.2023.08.02